Characterization of kaolin dispersion using acoustic and electroacoustic spectroscopy - Dohnalová Ž.; Svoboda L.; Šulcová P. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The objective of this work is the investigation of the kaolin dispersion by the ultrasonic techniques. In contact with aqueous solution clay minerals show cation - exchange properties and certain degree of dissolution or rather selective leaching of components. The work is divided into two main parts - determination of zeta potential and particle size distribution. The first part is focused on measuring of zeta potential. Effects of concentration of solid, different kind of electrolytes (0.01 M KCl, 0.01 M MgCl2 and 0.01 M CaCl2), pH and temperature of the dispersions are investigated. The isoelectric points (IEP) of kaolin suspension are about pH 4-5. Electrolytes containing monovalent cations such as K+ become zeta potential more negative compared to the values obtained with water. Such behavior is explained by the exchange of K+ ions with H+ ions in the system. When the electrolyte is formed by divalent cations such as Mg2+ or Ca2+, the values of zeta potential become less negative than zeta potential of kaolin in water. The second part is focused on the determination of particle size distribution with respect to dispersing conditions, such as the optimal dispersing agent (Na2SiO3, (NaPO3)6, Na4P2O7 or Busperse), time and power of ultrasonication and also the tracking of dispersion stability that is expressed by the measuring of particle size distribution during certain time period.